From Needy and Dependent to Independent Homo Ludens: Exploring Digital Gaming and Older People - Charles Musselwhite (Games and Culture, 2016)
This editorial piece presents a series of works within the field of gerontology and digital gaming. This edition came to fruition through colleagues having an interest in digital gaming and gerontology, and who wish to highlight the excellent work that is currently ongoing in this arena. Over the course of a year, the guest editors have been working with the journal and Sage to bring together this special edition in conjunction with the authors who initially proposed extended abstracts and submitted their articles for review. As guest editors we would like to say thank you to Professor Krzywinska, Sage and the authors for their assistance and submissions and to have being given the opportunity to execute an exciting project, which we hope the readers of the Games and Culture journal will enjoy.